2010
DOI: 10.1140/epjst/e2010-01313-1
|View full text |Cite
|
Sign up to set email alerts
|

The localization transition of the two-dimensional Lorentz model

Abstract: We investigate the dynamics of a single tracer particle performing Brownian motion in a two-dimensional course of randomly distributed hard obstacles. At a certain critical obstacle density, the motion of the tracer becomes anomalous over many decades in time, which is rationalized in terms of an underlying percolation transition of the void space. In the vicinity of this critical density the dynamics follows the anomalous one up to a crossover time scale where the motion becomes either diffusive or localized.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
89
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 54 publications
14
89
0
Order By: Relevance
“…Recent theoretical and simulation studies for a two-dimensional Lorentz model suggested that even though the non-universality of the transport exponent µ − β might originate from a sufficiently strong power-law singularity of the transition rate distribution between pores in three dimensions, narrow gaps responsible for the singularity would not be relevant in two dimensions and the transport exponent for lattices should be recovered. 18,19,21,23 We cannot conclusively determine whether the exponent µ-β is universal, but our analysis suggests this is the case if the system is ergodic. In order to investigate whether the transport exponent µ − β is universal, we estimate the transition rate (W) between two pores and its distribution (ρ(W )).…”
mentioning
confidence: 73%
“…Recent theoretical and simulation studies for a two-dimensional Lorentz model suggested that even though the non-universality of the transport exponent µ − β might originate from a sufficiently strong power-law singularity of the transition rate distribution between pores in three dimensions, narrow gaps responsible for the singularity would not be relevant in two dimensions and the transport exponent for lattices should be recovered. 18,19,21,23 We cannot conclusively determine whether the exponent µ-β is universal, but our analysis suggests this is the case if the system is ergodic. In order to investigate whether the transport exponent µ − β is universal, we estimate the transition rate (W) between two pores and its distribution (ρ(W )).…”
mentioning
confidence: 73%
“…This probably results from the completely different transport mechanism in our model and mechanisms proposed in continuous models (represented by the Lorentz model or by the DMD model) and in models based on a lattice. 33 The presence of a very high value of the exponent m can explain why the exponent a determined in experiments is considerably lower than 0.6-0.7. Thus, the scenario based on the DLL model can be closer to reality than other models, especially in membranes or cells.…”
Section: Discussionmentioning
confidence: 99%
“…This value is located between F c ¼ 0.22 found by Sung and Yethiraj 40 and the value F c ¼ 0.356 obtained by Bauer and coworkers using the Lorentz gas model. 33 …”
Section: Dynamic Behavior Near the Critical Point: The Percolationmentioning
confidence: 99%
See 1 more Smart Citation
“…All this is thoroughly reviewed in ref. [48]. We will now be more quantitative to be able to compare with the ABPs.…”
Section: Mean Squared Displacementmentioning
confidence: 99%